Anti-cancer potential of sting and stingless bee products: an updated systematic review - Poh, Lucky Wah Goh; Arnold Marshall Molujin; Roslina Jawan; Mohd Khalizan Sabullah; Suraya Abdul Sani; Jualang Azlan Gansau (Malaysian Society for Biochemistry and Molecular Biology, 2022)
Modern science and tools have found that traditionally used bee products could serve as alternative medicine and treatments. However, bee is under-studied and the bioactivity of sting and stingless bee products remain inconclusive. This systematic review aims to report a concise and updated finding on the potential anti-cancer activities of bee products. The article search strategy was performed according to PRISMA guide-lines and retrieved 425 articles. The authors assessed the titles, abstracts and full-text articles for suitability and data retrieval. The data from 16 articles were deliberated and summarized. Based on the information of this systematic review, bee products have great anti-cancer activity against various types of cancers and the activity is dependent on the type of product bee species. Bee species products can be further utilized and explored as an alternative medicine for cancer patients' treatments or healthy individuals as preventive medicine.